COMPARISON OF THE EFFECTIVENESS OF MGSO4 30 MG/KGBW AND INTRAVENOUS LIDOCAINE 1.5 MG/KGBW TO PREVENT POST-INTUBATION HEMODYNAMICS FLUCTUATION - MHD Mustafa LBS; Bambang Novianto P; R. Th Supraptomo (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: Intubation can cause hemodynamic fluctuations such as increases of systolic blood pressure, diastolic blood pressure, mean arterial pressure, and heart rate. MgSO4 and lidocaine can be used as premedication drugs to reduce the hemodynamic response to intubation. Objective: To compare the efficacy of intravenous MgSO4 30 mg/kgBW with lidocaine 1.5 mg/kgBW to prevent hemodynamic fluctuations after endotracheal intubation. Methods: This double-blind randomized controlled trial was conducted in 52 patients meeting the inclusion criteria who underwent surgery with general anesthesia using an endotracheal tube. These subjects were grouped into group A receiving intravenous MgSO4 30 mg/kgBW treatment and group B receiving intravenous lidocaine 1.5 mg/kgBW treatment. Hemodynamic fluctuation was recorded 1 minute after intubation. Results: Subjects receiving MgSO4 had lower increments of SBP (p≤0.001), DBP (p=0.001), MAP (p≤0.001), and HR (p=0.001) than those of receiving lidocaine. Conclusion: Intravenous MgSO4 30 mg/kgBW is more effective than intravenous lidocaine 1.5 mg/kgBW in preventing hemodynamic fluctuations after endotracheal intubation.